Donor age significantly influences the Raman spectroscopic biomolecular fingerprint of human pancreatic extracellular matrix proteins following collagenase-based digestion - Spiers, RM; Marzi, J; Brauchle, EM; Cross, SE; Vaughan, RH; Bateman, PA; Hughes, SJ; Schenke-Layland, K; Johnson, PRV (Elsevier, 2019)
Despite the enormous advances in the field of clinical pancreatic islet transplantation over the past two decades, the human islet isolation procedure remains suboptimal. Islets are extracted (isolated) from the exocrine tissue of donor pancreases using neutral protease (NP) and collagenase-based enzymes, which digest the extracellular matrix (ECM) scaffold surrounding human islets. This process remains highly variable and current isolation enzyme blends are ineffective at digesting pancreases from younger donors with low body mass indexes (BMI). However, age-related differences in pancreatic matrix digestion have not been studied in detail at the molecular level. To address this, we investigated ECM digestion in purified ECM proteins and in pancreatic tissue sections from younger (≤30 years; n = 5) and older (>55 years; n = 5) BMI matched donors, using Raman microspectroscopy (RMS). The Raman spectral profiles for purified collagens I, IV, VI and laminins were significantly altered following controlled enzyme treatment. Pancreatic cryosections were treated with Serva collagenase, NP, or the two enzymes combined, at clinically relevant concentrations. RMS demonstrated that the ECM at the islet-exocrine interface was differentially digested with respect to donor age. The action of collagenase was affected to a greater extent than NP. RMS is a powerful, marker-independent technology for characterising the human pancreatic ECM and demonstrating differences between donor types. Ongoing detailed studies using RMS will assist the development of donor-specific enzyme blends, increasing the overall success of human islet isolation and benefiting many people with type 1 diabetes worldwide.